The role of technology service contracts in the transfer of technical knowledge: A model of technical cooperation contract - Benhamadi, Amel (The International tax journal, 2026)
Technical assistance is a fundamental requirement that must be fulfilled to enable the recipient or importer to assimilate technical knowledge. This is particularly important given the recipient’s lack of experience in the transferred knowledge. Technical services enhance the recipient’s efficiency and technological capabilities when they include the necessary expertise, knowledge and information for acquiring the appropriate technology. They are a key part of the supplier’s commitment to transferring technical services to the importer.